Megalomania in Hawkin’s the Girl on the Train - Oktiva, Mirza; Chitra, Bima Prana (Universitas Harapan Medan, 2023)
This paper describes the megalomania in the novel The Girl on The Train by Paula Hawkin’s novel is shown by Tom to the women around him. The object of research in this thesis involves Tom's character, social life and moral values shown in the novel The Girl on The Train. This research uses qualitative descriptive research. The data obtained comes from the novel The Girl on The Train. This research focuses on Tom's character, how he treats the women around him, especially his ex-wife, where he has betrayed but he makes things as if he is the victim.